Biosolid soil application: Toxicity tests under laboratory conditions - Christofoletti, Cintya Ap. [UNESP]; Francisco, Annelise [UNESP]; Fontanetti, Carmem S. [UNESP] (Hindawi, 2012)
A large volume of generated sewage sludge makes its disposal a problem. The usage of sludge in agriculture is highlighted by a number of advantages. However, heavy metals and other toxic compounds may exercise harmful effects to soil organisms. This study evaluated the possible toxic effects of a biosolid sample, under laboratory conditions, for 30 days, using diplopods Rhinocricus padbergi and plants Allium cepa (onion) as test organisms. The data obtained demonstrated that the biosolid raw sample had genotoxic potential for Allium cepa root tip cells. In the diplopods exposed to biosolid sample, epithelium disorganization in the midgut and a reduction of the volume of the hepatic cells were observed after 7 days of exposure. After 30 days, the animals still showed a reduction of the volume of the hepatic cells, but in minor intensity. Allium cepa analysis showed genotoxicity, but this effect was reduced after 30 days of bioprocessing by diplopods. This study was important to know the effects as well as to determine how this waste could be applied concerning the soil living organisms and plants. © 2012 Cintya Ap. Christofoletti et al.
Keywords: Allium cepa; Animalia; Diplopoda; Rhinocricus padbergi